A Simple Dressing Fixation Method Following Harvest of the Ear Cartilage Graft. Issue 3 (May 2021) - Du, Hong; Zhang, Dong; Zong, Xianlei; Song, Guodong; Zhao, Jingyi; Yang, Changsheng; Guo, Xiaoshuang; Lai, Chenzhi; Jin, Xiaolei
Abstract : Abstract: Auricular cartilage is a common autologous graft material for rhinoplasty. Even though surgical techniques for the harvest of cartilage graft are well established, the management of the postoperative dressing fixation is still limited. Therefore, the authors propose a simple dressing fixation method in which gauze strips instead of gauze block or wet cotton, the suture of tie-over dressing fixed just through the cartilage rather than the full thickness of the auricle, a vaseline gauze interposed between the stitch knot and the skin and no additional pressure dressings postauricularly. No case of hematoma, infection and skin necrosis of the donor site was observed. This simple and reproducible technique provides perfect and homogeneous adhesion of the dressing all over the conchal cartilage while decreasing the risk of postoperative hematoma and discomfort.